The Anime Connection. Early Euro-Japanese Co-Productions and the Animesque: Form, Rhythm, Design - José Andrés Santiago Iglesias (Arts, 2018)
After European audiences had first contact with anime in the late 1970s, animated co-productions between domestic producers and Japanese studios emerged in the early 1980s, playing a lead role in standardizing anime aesthetics and hence contributing to the broader development of anime in Spain and other major European markets. These pioneering co-productions fostered the arrival of Japanese studios to the European broadcasting scene. However, its real impact on the popularization of anime is subject to debate. Appealing to a European audience, these series lacked some of the most recognizable features associated with anime as a larger medium. Nonetheless, in some of these animated productions there was an underlying animesque flair in the shape of conventionalized elements, character design, facial expressions, rhythm, camera action and tropes. Neither entirely domestic nor fully Japanese, these hybrid productions set up a ‘bridge’ between European and American animated visual language and anime mainstream features, thereby shaping the collective idea of what anime is for the first generation of viewers in Spain and Europe.